Optimization and analysis of heat and mass transfer parameters during hot air frying of chicken fillet - Fatemeh Keshavarziyan; Habibollah Mirzaei; Mahmoud Soltani Firouz; Alireza Sadeghi Mahonak; Majid Khanali; Hossein Ali Tash Shamsabadi (Applied Food Research)
This study investigated the effects of temperature, air velocity, and frying time on heat and mass transfer during the hot air frying of chicken fillets. Experiments were conducted at temperatures of 160, 180, and 200 °C, air velocities of 1.5, 2.5, and 3.5 m/s, and frying times of 600, 1200, and 1800 s. The key parameters including the Biot number, heat transfer coefficient, effective moisture diffusion coefficient, mass transfer coefficient, and final moisture ratio were analyzed using response surface methodology (RSM). The results indicated that higher temperatures significantly enhanced moisture diffusion (7.32 × 10⁻⁸ to 18.51 × 10⁻⁸ m²/s) and reduced the final moisture ratio (7.14–30.26 %). Air velocity played a critical role in improving heat and mass transfer, with the Biot number ranging from 0.048 to 0.088, the heat transfer coefficient from 4.54 to 7.32 W/m² °C, and the mass transfer coefficient from 5.33 × 10⁻⁵ to 16.14 × 10⁻⁵ m/s. Optimal frying conditions—180 °C, 2.5 m/s air velocity, and 20 min frying time—achieved a desirable balance of low moisture content (∼15 %) and controlled fat absorption while maintaining product quality. This study demonstrates that precise control of frying parameters optimizes both heat and mass transfer, enabling the production of healthier, high-quality fried products. The developed RSM models provide a reliable framework for process optimization, applicable in industrial and domestic frying processes.